TAXONOMY OF VISEAN MARINE CALCAREOUS ALGAE, FERNIE, BRITISH COLUMBIA (CANADA) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2006)
Reports a diverse microflora from the Late Viséan Opal Member, Fernie, Rocky Mountains, Canada.  A shallow-water limestone level yields forty identifiable taxa of green and red algae associated with  microproblematica.  Four  species are new :  Cabrieropora opalae, Cribrokamaena ferniensis, Koninckopora pachytheca and Moravammina ? enigmatica.  Inferred sedimentation is open marine, in normal salinity, from the middle part of the euphotic zone, within the fair-weather wave zone.  A semi-restricted lagoon located nearby provides floated calcispheres.  The high diversity is due to the excellent preservation of the thalli which were protected by a thin early coating of bacterial micrite.
Keywords: Carboniferous; Calcareous marine algae; Taxonomy; Diversity